Heavy social drinkers score higher on implicit wanting and liking for alcohol than alcohol-dependent patients and light social drinkers. (September 2015) - Tibboel, Helen; De Houwer, Jan; Spruyt, Adriaan; Brevers, Damien; Roy, Emmanuel; Noël, Xavier
Abstract: Background and objectives: Automatic hedonic ("liking") and incentive ("wanting") processes are assumed to play an important role in addiction. Whereas some neurobiological theories suggest that these processes become dissociated when drug use develops into an addiction (i.e., "liking" becomes weaker, whereas "wanting" becomes exaggerated; e.g., Robinson & Berridge, 1993), other theories suggest that there is a linear relationship between these two processes (i.e., both "liking" and "wanting" increase equally; e.g., Koob & Le Moal, 1997). Our aim was to examine "wanting" and "liking" in three groups of participants: alcohol-dependent patients, heavy social drinkers, and light social drinkers. Methods: Participants performed two different single target implicit association tests (ST-IATs; e.g., Bluemke & Friese, 2007) and explicit ratings that were designed to measure "liking" and "wanting" for alcohol. Results: Our results are in sharp contrast with the theories of both Robinson and Berridge and Koob and Le Moal: heavy drinkers had higher scores than light drinkers and alcohol-dependent patients on both the wanting ST-IAT and the liking ST-IAT. There were no differences between alcohol-dependent patients and light drinkers. Explicit ratings mirrored these results. Limitations: These findings suggest that our ST-IATs are not valid measures of "wanting" and "liking". Instead, they might assess more complex knowledge regarding participants' experiences and goals. Conclusions: These findings suggest that the relationship between drug consumption and appetitive drug associations is not linear, highlighting the importance of testing both sub-clinical and clinical samples in future research. Highlights: Incentive sensitization theory suggests that, in addiction, wanting and liking are dissociated. We used different implicit measures to assess implicit wanting and liking in three groups. We tested heavy social drinkers, light social drinkers and alcohol-dependent patients. Results showed that light social drinkers and patients differed from heavy social drinkers. Both light drinkers and patients had significant negative scores on implicit wanting and liking.